The development of the antihydrogen beam detector and the detection of the antihydrogen atoms for in-flight hyperfine spectroscopy. (July 2015) - Nagata, Y; Sauerzopf, C; Capon, A; Kuroda, N; Abo, Y; Diermaier, M; Dupre, P; Higashi, Y; Ishikawa, S; Kaga, C; Leali, M; Malbrunot, C; et al.
Synopsis: We have been developing ground-state antihydrogen atomic beams to test CPT symmetry via in-flight hyperfine spectroscopy. A new antihydrogen beam detector has been developed. The overview of the experiment, the detail of the detector and latest results will be presented.